2015
DOI: 10.1186/s13054-015-1029-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with bacteremia in the setting of methicillin-resistant Staphylococcus aureus pneumonia: a retrospective cohort study

Abstract: IntroductionMethicillin-resistant Staphylococcus aureus (MRSA) remains an important pathogen in pneumonia. Bacteremia may secondarily complicate MRSA pneumonia. The epidemiology and outcomes associated with bacteremia in the setting of MRSA pneumonia are unknown. We sought to describe the prevalence of bacteremia in MRSA pneumonia and its impact on hospital mortality and length of stay (LOS).MethodsWe conducted a single-center retrospective cohort study (2008–2013) including adult patients hospitalized with pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
1
14
2
Order By: Relevance
“… 14 In addition, an analysis of variables associated with clinical success, using data from a randomized trial, found that treatment with linezolid was more likely to be successful (OR=1.55; 95% CI=1.01–2.34). 15 The results of our study, which confirmed the efficacy of antimicrobials other than vancomycin as initial treatment of MRSA infections, of the lung in particular, are concordant with the results of these meta-analyses.…”
Section: Discussionsupporting
confidence: 90%
“… 14 In addition, an analysis of variables associated with clinical success, using data from a randomized trial, found that treatment with linezolid was more likely to be successful (OR=1.55; 95% CI=1.01–2.34). 15 The results of our study, which confirmed the efficacy of antimicrobials other than vancomycin as initial treatment of MRSA infections, of the lung in particular, are concordant with the results of these meta-analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Comparison with data from previous daptomycin studies is challenging due to the exclusion of BSI secondary to pneumonia from these studies (9-11). One-third of this cohort was comprised of patients with a lower respiratory tract source of infection, which carries a high risk of mortality (25,26). Nonetheless, the proportion of patients who experienced failure was similar to that in a recently reported evaluation of daptomycin for MRSA BSI (11).…”
Section: Discussionmentioning
confidence: 57%
“…4 Estimates of Excess Length of Stay of Hospital/ICU Stay Caused by Antimicrobial Resistance. (i) - (iii) denote different methods used in a single study [ 48 51 , 58 , 59 , 76 , 122 , 123 , 132 , 133 ] …”
Section: Resultsmentioning
confidence: 99%
“…For those that did estimate excess length of stay, it was expected (given previous literature [ 28 ]) that multistate model length of stay estimates compared to those found using alternative methods would be more conservative. However, this review found that multistate model estimates for length of stay for MRSA infection and MRSA bloodstream infection were higher than those using stepwise analysis and regression analysis [ 48 , 50 , 58 , 59 ]. This is likely due to the fact that the described studies were set in different countries (Australia, Germany, Switzerland and US) and were mainly single centre studies, and so less externally valid.…”
Section: Discussionmentioning
confidence: 99%